2014
DOI: 10.1111/1744-9987.12169
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dialysis Duration on the Outcome of Living Kidney Transplantation

Abstract: Previous studies have reported negative impacts of long-term dialysis on kidney transplantation (KTx) outcomes. However, advances in surgical techniques, immunosuppressive therapies, and post-transplant monitoring have led to an impressive increase in patient and allograft survival. Thus, the number of KTx among patients on long-term dialysis is increasing. We evaluated the influence of dialysis duration on the outcome of living donor KTx. Between January 2000 and October 2011, we performed 1098 first KTx from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Therefore, pretransplant duration of dialysis also varies between countries. While some studies reported that longterm dialysis negatively affects the results of KT, others showed that there is no difference in terms of graft or patient survival with the length of dialysis treatment (3,4). Studies from the USA have shown that KT performed after a long dialysis period was associated with a higher risk of graft failure and death compared to preemptive KT (5).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pretransplant duration of dialysis also varies between countries. While some studies reported that longterm dialysis negatively affects the results of KT, others showed that there is no difference in terms of graft or patient survival with the length of dialysis treatment (3,4). Studies from the USA have shown that KT performed after a long dialysis period was associated with a higher risk of graft failure and death compared to preemptive KT (5).…”
Section: Discussionmentioning
confidence: 99%
“…This study included 6887 patients who were divided into four groups based on the duration of dialysis: preemptive SPK or PSPK (group A), 0‐2 years of dialysis (group B), 2‐5 years of dialysis (group C), and >5 years of dialysis (group D). Long‐term dialysis was defined as 2‐5 years or >5 years of dialysis 8 . The duration of dialysis was calculated as the transplant date minus the date on which dialysis was started.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Helantera and his colleagues demonstrated that long‐term preoperative dialysis duration was associated with reduced patient survival, but not reduced graft survival after renal transplantation 11 . In contrast, Kohei et al 8 reported that no significant difference was observed in patient or graft survival for groups with different pre‐transplant dialysis durations. However, there are only a few reports on the impact of pre‐transplant dialysis duration on SPK transplant outcomes in T1DM patients 12,13 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations